2015
DOI: 10.1002/cmdc.201500218
|View full text |Cite
|
Sign up to set email alerts
|

Novel Triazolopyrimidine‐Derived Cannabinoid Receptor 2 Agonists as Potential Treatment for Inflammatory Kidney Diseases

Abstract: The cannabinoid receptor 2 (CB2) system is described to modulate various pathological conditions, including inflammation and fibrosis. A series of new heterocyclic small-molecule CB2 receptor agonists were identified from a high-throughput screen. Lead optimization gave access to novel, highly potent, and selective (over CB1) triazolopyrimidine derivatives. A preliminary structure-activity relationship was established, and physicochemical properties in this compound class were significantly improved toward bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 45 publications
3
32
0
Order By: Relevance
“…There was, however, accumulation of SMM-295 in the kidney, which could obviate the rapid decrement of circulating drug and provide more opportunity for renal cell signal activation, particularly during times of renal injury that would negatively impact clearance of exogenous drugs. Consistent with our study, Nettekoven et al (2016) showed that their newly synthesized CB2 receptor agonist could reduce circulating creatinine after renal IRI. Moreover, a partial CB2 agonist, methyl]-5-fluoro-2-pyridinyl]phenyl]methyl]-2,4-imidazolidinedione), was capable of attenuating cisplatin-induced tubular damage by reducing oxidative stress and inflammation in mice (Mukhopadhyay et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…There was, however, accumulation of SMM-295 in the kidney, which could obviate the rapid decrement of circulating drug and provide more opportunity for renal cell signal activation, particularly during times of renal injury that would negatively impact clearance of exogenous drugs. Consistent with our study, Nettekoven et al (2016) showed that their newly synthesized CB2 receptor agonist could reduce circulating creatinine after renal IRI. Moreover, a partial CB2 agonist, methyl]-5-fluoro-2-pyridinyl]phenyl]methyl]-2,4-imidazolidinedione), was capable of attenuating cisplatin-induced tubular damage by reducing oxidative stress and inflammation in mice (Mukhopadhyay et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…Activation of CB2R reduces inflammation in various inflammatory-associated diseases including nephropathy and cystitis 15 , 17 , and blunts the development of UUO-induced renal fibrosis 20 , 22 . To explore the relationship between celastrol treatment and CB2R function, we measured CB2R expression levels in kidney tissues of mice after UUO surgery.…”
Section: Resultsmentioning
confidence: 99%
“… 20–23 Despite the preponderance of evidence implicating the EC system and ECs in nonrenal IRI, data on the role of ECs in renal IRI remain sparse. 24 , 25 In addition, most of the studies examining the role of the EC system in renal injury focus on the effects of the activation or inhibition of the CB receptors and do not provide data on the tissue level of the endogenous ligands for these receptors, 2-AG and AEA. In this study, we show for the first time that renal IRI leads to a significant increase in renal level of 2-AG, one of the major activators of the EC system.…”
Section: Introductionmentioning
confidence: 99%